Surgical intervention for vertebral osteomyelitis in a calf. Issue 6 (20th June 2019) - Shivapour, Sara K.; Jackson, Nicole D.; Schleining, Jennifer A.; Kreuder, Amanda J.; Miles, Kristina G.; Jeffery, Nicholas D.
Abstract: Objective: To report the surgical treatment and outcome of a non‐ambulatory calf with cervical vertebral ostoeomyelitis. Study design: Clinical report. Sample population: One 3.5‐month‐old female mixed‐breed calf with tetraparesis of 3 months duration. Methods: After computed tomography‐guided bone biopsy, a bacterial osteolytic lesion within the body of the fourth cervical vertebrae (C4) and resultant pathologic compression fracture clinically resulting in full tetraparesis was diagnosed in the calf. Culture results from the lesion within C4 confirmed a diagnosis of Trueperella pyogenes . Results: Poor response to medical management justified surgical debridment of the lesion in C4 and subsequent stabilization of the cervical vertebral column. A three‐part procedure was performed including (1) debridement of the C4, (2) bilateral ventral vertebral stabilization from C3 to C5, and (3) placement of ampicillin‐impregnated plaster of Paris beads within the body of C4. With postoperative physical rehabilitation, the calf regained full ambulatory function. At 1‐month follow‐up, the calf remained ambulatory with mild proprioceptive ataxia and no evidence of implant failure. At annual recheck, the calf had gained 208 kg and remained fully ambulatory with no residual neurologic deficits. Conclusion: Surgical intervention and use of antibiotic‐impregnated implants offered a viable alternative to long‐term medical management of vertebral osteomyelitis in the calf reported here. Clinical significance: This case identifies surgical intervention as a potential means for improving outcomes in a historically fatal condition of production animals.